(untitled) (Nordic Journal of Practical Theology, 2019)
The article presents a qualitative study on open and announced healing practices in three Christian Lutheran fellowships in Norway. Using observation and interviews, we explore characteristics of such healing practices and how the practices are explained and interpreted by some of the leaders involved. Practice theory and theories about power are applied abductively to analyse the material. We indicate that different power dynamics are in play between the leaders responsible for the intercessions and the participants. The leaders negotiate between positions, believing themselves to convey power from God as well as power through their own (lack of) ability to heal and control the outcome. Dialogue between the leaders and the participants is limited (power with) and we consider how this safeguards the well-being of the vulnerable participants.